Learning During the Covid-19 Pandemic and Cultural Transformation in the Indonesian Education System - Rijal, Akmal; Egok, Asep Sukenda; Satria, Tio Gusti (Jurnal Pendidikan Indonesia, 2022)
This research is motivated by efforts to provide recommendations and find ways to learn learning systems in adaptation to new habits. This study uses a qualitative research method with a phenomenological approach with data collection techniques through involved observation or participatory observation, in-depth interview techniques, and document analysis. The research subjects were the principals, teachers, students, and parents of students in grades 1 to 6 as many as 200 people with a sample of 28 people. The results showed that the learning process during the pandemic is online and face-to-face in class with health protocols, students have difficulty doing assignments given by the teacher, internet network disturbances, cannot concentrate, mostly play, difficult to discipline in health protocols, and teachers make fun online learning techniques so that students do now not experience bored in reading at home with video media. This study concludes is that new habits in teacher learning must be creative in teaching by using personalized technology according to needs, disseminating awareness of health protocols, the government, parents, and the community are always disciplined and control health protocols, and support and develop facilities and infrastructure.